Coda: Exploring Male Depression and the Stigma Associated with Depression - Sheena Sugiarto (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This creative thesis aims to show depressive symptoms in men, the stigma associated with depression, and the way stigma impacts depressed individuals by means of a screenplay. Using drama as the genre and psychological drama as the sub-genre, I exploit the emotional strain of the main character to show the struggles of male depression as well as the brutal consequences of stigma. The screenplay, titled Coda, follows Arya, a boy who struggles with depression and stigma associated with depression. As the story progresses, Arya’s mental health condition increasingly declines. Arya exhibits depressive symptoms although they are not typically recognized as depression. These include frequent irritability and inappropriate anger, escapists behavior, physical symptoms, problems with drug use, and risky behavior. In addition to that, Arya also experiences personal stigma from his family, which gradually affects their relationship and ultimately leads him to impulsively commit suicide. Keywords: Male depression, stigma, impact